Стеклянная гора: романы - Авижюс Йонас Казимирович (1988)
Экземпляры: Селтинская районная библиотека (аб) (20191118) / Инвентарный номер: 134667 / Цена: / Авт.знак: А20 / ГРНТИ: 17.82.30 / ББК: 84(4Лит)